Tanggung Jawab Pendeteksian Kecurangan sebagai Pencegahan Kegagalan Audit (Studi pada Kantor Akuntan Publik di Jakarta) - Annisa Adha Minaryanti; Mochammad Ridwan (Faculty of Economics and Business, University of Pasundan, 2015)
This study aims to determine how the impact of fraud detection responsibility to the prevention of audit failure are. The object of this study includes responsibility of fraud detection as an independent variable whose influence the dependent variable (dependent), called the audit failure prevention. Method used in this study is the Correlative relationship research method, alongside the clausal relation as the type of relation between variable studied in this study. These variables were analyzing using the descriptive statistics and regression to test the hypothesis. The data collected obtained through questionnaires and auditors as respondents at Accounting Firm in Jakarta. After obtaining data, results tended to show that responsibility for fraud detection have significant effect on the audit failure prevention.